Emerging Attitudes Regarding Decriminalization: Predictors of Pro-Drug Decriminalization Attitudes in Canada - MacQuarrie, Amy L. (Journal of drug issues, 2022)
Canada and the United States have recently evaluated the decriminalization of drugs as multiple provinces and states put motions forward to consider drug decriminalization legislation. The influence of factors such as demographics, substance use, perceived substance use risk, and personality have not been widely studied in predicting attitudes toward drug decriminalization. A total of 504 participants were drawn from university (n = 269, 53.37%) and community samples (n = 235, 46.63%) through online social media groups and posts (i.e., Facebook, Twitter, Reddit, etc). Analyses indicated that male gender, single or non-married relationship status, living outside of Atlantic Canada, higher problematic alcohol use scores, lower Extraversion, higher Open-mindedness, and lower perceived risk of using substances emerged as significant predictors of support for drug decriminalization. These findings have important implications as public attitudes toward a substance influence drug policy.